THEMES IN JAMES JOYCE’S SHORT STORY “DUBLINERS” - Rinkarsi, Jhon; Suhatmady, Bibit (BASTRA : Jurnal Penelitian Pendidikan Bahasa dan Sastra, 2014)
The purpose of this study was to know the themes found in James Joyce’s short story “Dubliners” and to know how the themes are reflected by the characters in James Joyce’s short story “Dubliners” Related to the purpose of the study, the writer used descriptive qualitative design. The data for this research is the form of text extraction from the short stories taken from the Dubliners, James Joyce Collection. The Flow Model that proposed by Miles and Huberman was used in this study to analysethe data. The result of this study showed that that there are fifteen different themes in fifteen short stories of Dubliners, they are The death of The Priest in The Sisters, Adventure of the schoolboy in An Encounter, A boy’s struggle for a girl in Araby, Sacrifice from a young girl in Eveline, An ambition of a young man in After The Race, A man who wanted to prove something in Two Gallants, Desire to escape in The Boarding House, A man’s frustration with his current life in A Little Cloud, A miserable drunk worker in Counterparts, compassionate woman in Clay, A forbidden love in A Painful Case, The canvassers talk about their candidates in Ivy Day In The Committee Room, An ambitious mother in A Mother, Men’s effort for their friend in Grace, and His wife’s first love in The Dead. The theme was reflected commonly by the main character from each short stories. It might come from the dialogue or conversation they made with other characters or the narration from the story itself.